Study of perinatal factors in children with developmental delay - Charan, Goli Sri; Vagha, Jayant (International Journal of Contemporary Pediatrics, 2016)
Background: Birth history gives important information in children with developmental delay. Developmental challenge in children is an emerging problem across the globe, which is largely associated with improved neonatal survival. The present study highlights the importance of birth history in children with developmental delay in our hospital. The objective of this study was to study the perinatal events in children with developmental delay. Methods: Observational descriptive study was conducted on children between 6 months to 5 years who were admitted in Pediatric wards with suspected history of developmental delay. DDST II scale was performed on these children and children who failed on Denver II scale were recruited into the study. Birth history was noted in detail, if available, documentation of birth events was asked for and noted. Developmental history with developmental quotient (DQ), were noted in detail. Results: 135 children had developmental delay, 113 (83.70%) were born by vaginal delivery and 22 (16.30%) were born by caesarian section, 46 (34.18%) had no cry at birth and remaining 89 (65.92%) had normal cry at birth. 104 (77.04%) were born by term gestation and 31 (22.96%) were born preterm. Birth weight was normal in 78 (57.7%) children, LBW was seen 47 (34.81%) and 5 children each with VLBW and ELBW and 35 (25.93%) were IUGR. On comparing the children born gestational age and birth body weight with all four domains, there was no significant difference. Conclusions: Global developmental delay was more common in children born at preterm, low birth weight, IUGR and children who had birth asphyxia. Birth weight and gestational age did not significantly affect any particular domain of development.